Investigation of deformation mechanisms in nanocrystalline metals and alloys by in situ synchrotron X-ray diffraction - Lohmiller, Jochen Andreas (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2013)
In this work, different nanocrystalline metals and alloys were investigated by a synchrotron-based in situ XRD mechanical testing technique in order to investigate the dominant deformation mechanisms. All tested samples show a succession and coexistence of several mechanisms, regardless of grain size, loading condition, or sample geometry. However, the relative shares of the individual mechanisms strongly vary and depend on parameters such as grain size, sample purity, and alloy composition.